Do Textured Insoles Affect Postural Control and Spatiotemporal Parameters of Gait and Plantar Sensation in People With Multiple Sclerosis?. Issue 1 (19th August 2014) - Kalron, Alon; Pasitselsky, Diana; Greenberg‐Abrahami, Michal; Achiron, Anat
Abstract: Background: Balance and gait deficits are common in people with multiple sclerosis (MS). Physical interventions directed at improving balance and walking abilities have been implemented using various approaches. Nonetheless, no mode of training has been universally agreed upon. Objectives: To determine whether textured insoles have immediate effects on postural control and spatiotemporal parameters of gait and plantar sensation in people with people with MS and to explore effects 4 weeks after insole wear as to whether any immediate effects are maintained over time. Design: Within‐subject experimental study with a 4‐week intervention phase. Settings: Multiple Sclerosis Center, Center of Advanced Technologies in Rehabilitation, Sheba Medical Center, Tel‐Hashomer, Israel. Participants: Twenty‐five relapsing‐remitting patients diagnosed with MS, 16 women and 9 men, aged 49.6 years (standard deviation = 6.5 years). Intervention: Textured insoles customized according to foot size and adapted to the participant's casual shoes. Main outcome measures: Spatiotemporal parameters of gait and center of pressure (CoP) excursions during static postural control were studied using the Zebris FDM‐T Treadmill. Light‐touch and pressure‐sensation thresholds were determined using the Semmes‐Weinstein monofilaments test. Results: Textured insoles did not alter static postural control parameters when examined with eyes open. Examination during the eyes‐closed task demonstrated an immediate reduction in the CoP path length (298.4 mm, standard error = 49.7 mm, versus 369.9 mm, SE = 56.3 mm; P = .04) and sway rate (12.0 mm/s, standard error = 1.4 mm/s, versus 15.1 mm/s, standard error = 1.6 mm/s; P = .03) after insertion of the textured insoles compared to casual shoes alone. These findings were maintained at termination of the insole 4‐week intervention period. In terms of spatiotemporal parameters of gait, differences were not observed between casual shoes and shoes with textured insoles at baseline. Likewise, no differences were observed between initial and concluding gait trials. Significant differences in plantar sensitivity measures were not observed after the insole 4‐week intervention phase. Conclusions: Although there were improvements in some aspects of balance, the efficacy of textured insoles in the MS population remains unclear.